Standardization of Micropropagation for Four Hybrids of Coffea arabica Through Direct Somatic Embryogenesis - Marileydi Zuta-Puscan; Jegnes Benjamín Meléndez-Mori; Eyner Huaman-Huaman; Yoiner Kalin Lapiz-Culqui; Reyna Stefani Mego-Pérez; Manuel Oliva-Cruz (Agronomy)
Direct somatic embryogenesis represents a fundamental tool for obtaining genetically homogeneous clones; however, its commercial scaling faces critical challenges at various stages of the process. In this study, a protocol is standardized for the induction and germination of somatic embryos from leaf segments, rooting, and acclimatization of four Coffea arabica hybrids: Casiopea, Excelencia, H3, and Milenio. The results show that the Casiopea and Excelencia hybrids achieve the highest induction rates (71.64% and 74.43%) and embryo production (8.74 and 10) per explant in the M1 medium, while these values are significantly lower for H3 and Milenio. In addition, the germination and conversion of embryos into plantlets are more efficient in the woody plant medium (WPM), while rooting is optimized using indole-3-butyric acid (IBA) concentrations between 1 mg L−1 and 3 mg L−1, regardless of the hybrid. During the acclimatization phase, plantlets treated with mycorrhizae exhibit improved morphological, physiological, and nutritional indicators, achieving a superior quality according to the Dickson index. These findings significantly reduce production times by establishing precise standards for each genotype, thereby overcoming existing gaps in production protocols and providing a solid foundation for industrial growth.